Facial skin injuries caused by individual protectors in the combat to covid-19 - PEREIRA,Francine Queiroz (2022)
ABSTRACT The single-stranded ribonucleic acid coronavirus is the seventh known member of the Coronaviridae family to infect humans. The droplets and aerosols that are suspended in the air with the virus can be transmitted by contact with the oral, nasal and eye mucosa, which can cause severe acute respiratory syndrome. Due to the outbreak of the new coronavirus disease, the constant use of personal protective equipment by health professionals has become necessary, as the virus has a rapid and widespread spread. But, unexpectedly, the coronavirus outbreak brought another concern, the emergence of facial injuries due to the continuous and inappropriate use of these individual protectors, harming the health of these professionals. An alternative to alleviate and prevent such injuries would be the use of prophylactic creams and dressings in places where there is pressure caused by these equipment, as well as relieving the loads generated by them, at intervals that do not exceed 4 hours. Therefore, this literature review aimed to report the potential for the emergence of facial injuries caused by the continuous and inappropriate use of PPE, highlighting the most affected areas, the risks to the health of the professional, prevention and treatment, through the electronic consultation based on of data, PUBMED, SCOPUS and Bireme/BVS.